The optimal timing of Ambu® Aura onceTM Laryngeal Mask Airway insertion with propofol induction - Wei Chen; Rebecca Downey; Richard Sheu; Hui Qu; Iwona Bonney; Peishan Zhao (Global Journal of Anesthesiology - Peertechz Publications, 2021)
Background: Laryngeal Mask Airway (LMA) is usually inserted without muscle relaxants, which requires good jaw relaxation. Previous studies have focused on creating the optimal condition for LMA insertion with different anesthetic adjuncts. This study is to determine whether the time interval between induction and insertion influences placement conditions. Insertion of LMA at the best time interval may decrease the complications associated with LMA placement.  Methods: This is a prospective randomized study with a total of 198 ASA I or II patients assigned to three groups: Group 0", Group 60" and Group 90", with number representing the seconds from loss of eye lash reflex (ELR) to LMA insertion. All patients were pretreated with intravenous midazolam 2 mg and fentanyl 1 mcg/kg at a given time. Induction was achieved with 2.5 mg/kg propofol. Ambu® AuraOnceTM LMA was placed by a blinded anesthesiologist who also assessed the condition for LMA insertion based on a score system. The primary outcome is to find the optimal condition for LMA insertion in each group. The conditions were defined as optimal or non-optimal based on the total score of 6 or > 6, respectively. Results: The percentage of the optimal condition was significantly different amongst the three groups (p = 0.031). The optimal condition was 68% in Group 60", that was significantly higher than 45% in Group 0" (p = 0.008), but not than 58% in Group 90" (p=0.207).  Conclusions: Induction of general anesthesia with 2.5 mg/kg of propofol, with pre-administration of midazolam and fentanyl, provided the highest percentage of optimal condition of LMA insertion at 60 seconds after loss of ELR.